Intraseasonal Air–Sea Interaction Over the Southeastern Indian Ocean and its Impact on Indian Summer Monsoon - Meng, Ze; Zhou, Lei; Qin, Jianhuang; Li, Baosheng (Frontiers in Marine Science, 2022)
The weak monsoon rainfall simulation in the CMIP6 models calls for further process understanding about the Indian summer monsoon (ISM), especially the intraseasonal variabilities. Here, the remote forcing from the Southern Hemisphere on the Indian summer monsoon is examined. Over the southeastern Indian Ocean (SEIO), intraseasonal warm SST anomalies can induce low-level southeasterly wind anomalies and accelerate the background southeasterly wind. According to the WES/WHISE mechanisms, the wind acceleration gives rise to the positive anomalies of surface latent heat flux (LHF). The intraseasonal wind anomalies propagate equatorward along with the background southeasterlies, the positive LHF increases the moist static energy over the equator. As a result, deep convections are reinforced over tropics, which strengthen the northward-propagating monsoon intraseasonal oscillations. During boreal summer, the northward intraseasonal oscillations prompts enhanced rainfall events over the monsoon region. Current results indicate the inter-hemispheric impacts as an inevitable contributor to the heavy precipitation during ISM in the Northern Hemisphere. In CMIP6, the models with better SST simulations over SEIO can have stronger equatorial rainfall as well as more realistic northward propagation. The unsatisfactory simulations of CMIP6 are associated with the defective ocean-atmosphere interaction over SEIO, and one clue is the feeble variances of intraseasonal oceanic signals over SEIO, which is far from the observation. This research offers a new perspective on the chronic dry monsoon bias in the Northern Hemisphere, the cross-equatorial process and the bias of intraseasonal oceanic variation over SEIO deserve further attention in the coupled models.